Malignant melanoma of the vulva with metastases to the urethra in a 64-year-old female patient – case report - Jach, Robert; Przybylska, Paulina; Mika, Marcin; Galarowicz, Bartłomiej; Radoń-Pokracka, Małgorzata; Basta, Paweł; Huras, Hubert (Menopause Review/Przegląd Menopauzalny, 2011)
Melanoma of the vulva comprises around 3-4% of all melanoma cases in women, very rarely appearing before the age of 50. It belongs to the group of rare tumours in this location, comprising 8-10% of vulva tumours, and the estimated frequency of vulvar melanoma occurrence is 0.10/100 000 women-years. Among the factors that can predispose to developing melanoma of the vulva, we can distinguish chronic inflammatory diseases, virus infections (including HPV virus), factors causing vulva irritation and genetic susceptibility. The majority of melanomas of the vulva develop “de novo”, but they can also develop on the basis of previously existing pigmentary birthmarks. Most frequently, during physical examination pigmentary changes in the area of the vulva are found. However, in around 30% of cases melanoma does not have pigmentary traits. The depth of infiltration (invasion) is the crucial prognostic histological factor in melanoma. The treatment is based on surgery, the extent of which depends on the stage of tumour advancement. Supplemental treatment makes use of interleukin-2, interferon alpha, dacarbazine or paclitaxel with cisplatin or carboplatin. The case of a 64-year-old female patient with melanoma of the vulva area, who despite surgical treatment based on partial excision of the vulva with lymph glands and keeping a margin of healthy tissues, as well as supplemental therapy with interferon alpha, and who after a year was diagnosed with reoccurrence of the tumour in the area of the distal part of the urethra, is presented below. Continuation of the treatment is based on surgical excision of the front part of the vulva together with the distal part of the urethra and adjuvant chemotherapy treatment according to the docetaxel/carboplatin combination.